Enhancing care transitions intervention with peer support to improve outcomes among older adults with co-occurring clinical depression: a pilot study. Issue 4 (2nd October 2021) - Conner, Kyaien O.; Gum, Amber M.; Schonfeld, Lawrence; Kosyluk, Kristin; Anderson, Erica; Baker-Douglan, Jamie; Beckstead, Jason; Meng, Hongdao; Brown, Charlotte; Reynolds, Charles F.
ABSTRACT: The Care Transitions Intervention (CTI) is an evidence-based intervention aimed at supporting the transition from hospital back to the community for patients to ultimately reduce preventable re-hospitalization. In a pilot randomized controlled trial, we examined the preliminary effectiveness of an Enhanced Care Transitions Intervention (ECTI), CTI with the addition of peer support, for a racially/ethnically diverse sample of older adults (age 60+) with co-morbid major depression. We observed a significant decline in health-related quality of life (HRQOL) after being discharged from the hospital among those who received CTI. Additionally, those who received ECTI either maintained HRQOL scores, or, saw improvement in HRQOL scores. Findings suggest the Enhanced Care Transitions Intervention can maintain or improve HRQOL and reduce disparities for older participants from diverse racial/ethnic backgrounds with clinical depression.